ASSESSMENT OF SOCIAL-HYGIENIC FACTORS, DIETARY PATTERNS, AND PHYSICAL ACTIVITY IN WOMEN WITH METABOLIC SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Metabolic syndrome (MetS) is a fundamental factor in cardiometabolic risk and reproductive dysfunction among women. This review article analyzes the impact of socio-hygienic environments, dietary habits (alimentation), and hypodynamia (physical inactivity) on the development of MetS. Research findings indicate that chronic psychosocial stress and unfavorable social conditions significantly escalate the risk of MetS. While the prevalence of high-calorie foods in the diet increases the risk, a diet rich in fruits and vegetables combined with regular physical exercise serves as an effective protective measure. The article highlights the necessity of a comprehensive approach to promoting a healthy lifestyle and reducing MetS risks in women.